Vegetation analysis and species diversity of the invasive plant Heliotropium curassavicum growing naturally in heterogeneous habitats - Hamdy, Marium; El‐Halawany, El‐Sayed F.; Elsayed, Ashraf; El‐Amier, Yasser A. (Journal of Phytology, 2022)
Heliotropium curassavicum is an invasive annual weed plant that spreads quickly, especially on disturbed saline soils and coastal locations in arid and semiarid habitats. This study aimed to assess the vegetation composition of invasive plant H. curassavicum. The soil factors and associated species of this plant were studied in natural coastal desert habitats (northern Nile delta coast) and inland habitats (farrow land and canal bank habitats). The floristic composition revealed the occurence of 109 species (67 annuals, 2 biennials and 40 perennials) belonging to 86 genera and related to 29 families. Asteraceae, Poaceae, Chenopodiaceae, and Fabaceae (53.21 % of all species reported) are the most abundant families. Therophytes and cryptophytes are the mainly abundant life forms and the Mediterranean chorotype is the most representative. The cluster analysis of stands expressed four vegetational groups (A, B, C and D). The most dominant species with group A was Polypogon viridis, with group B was H. curassavicum, with group C (the largest one) was Cynodon dactylon and H. curassavicum and with group D was Phragmites australis. Diversity indices expressed more richness and evenness of vegetation group B (H. curassavicum communities). The major soil factors influencing the studied invasive species are soil texture, WHC, organic carbon, cations (Na+, K+, Ca++, and Mg++), and SAR.